GintAMT3 – a Low-Affinity Ammonium Transporter of the Arbuscular Mycorrhizal Rhizophagus irregularis - Calabrese, Silvia; Pérez-Tienda, Jacob; Ellerbeck, Matthias; Arnould, Christine; Chatagnier, Odile; Boller, Thomas; Schüßler, Arthur; Brachmann, Andreas; Wipf, Daniel; Ferrol, Nuria; Courty, Pierre-Emmanuel (Frontiers in Plant Science, 2016)
Nutrient acquisition and transfer are essential steps in the arbuscular mycorrhizal (AM) symbiosis, which is formed by the majority of land plants. Mineral nutrients are taken up by AM fungi from the soil and transferred to the plant partner. Within the cortical plant root cells the fungal hyphae form tree-like structures (arbuscules) where the nutrients are released to the plant-fungal interface, i.e. to the periarbuscular space, before being taken up by the plant. In exchange, the AM fungi receive valuable carbohydrates from the plant host. Besides the well-studied uptake of phosphorus (P), the uptake and transfer of nitrogen (N) plays a crucial role in this mutualistic interaction. In the AM fungus Rhizophagus irregularis (formerly called Glomus intraradices), two ammonium transporters (AMT) were previously described, namely GintAMT1 and GintAMT2. Here, we report the identification and characterization of a newly identified R. irregularis AMT, GintAMT3. Phylogenetic analyses revealed high sequence similarity to previously identified AM fungal AMTs and a clear separation from other fungal AMTs. Topological analysis indicated GintAMT3 to be a membrane bound pore forming protein, and GFP tagging showed it to be highly expressed in the intraradical mycelium (IRM) of a fully established AM symbiosis. Expression of GintAMT3 in yeast successfully complemented the yeast AMT triple deletion mutant (MATa ura3 mep1Δ mep2Δ::LEU2 mep3Δ::KanMX2). GintAMT3 is characterized as a low affinity transport system with an apparent Km of 1.8 mM and a Vmax of 240 nmol-1 min-1 108 cells-1, which is regulated by substrate concentration and carbon supply.